Nonlinear Behavior of Buildings Subjected to Monotonically Increasing Lateral Load (Proceedings of Faculty of Civil Engineering, 2020)
The paper presents a parametric study and the application of the nonlinear N2 method for the evaluation of the seismic behavior of a four-story and an eight-story reinforced concrete frame structure subjected to seismic action. Three distributions of the horizontal loading of the structure by seismic forces were used in the study: triangular (linear), uniform and modal. The influence of the P-delta effects on seismic behavior of the observed structures was also investigated.
Keywords: pushover method; N2 method; seismic analysis; nonlinear behavior; building; P-delta effect; plastic hinge